Monoclonal Antibodies and their Target Specificity Against SARS-CoV-2 Infections: Perspectives and Challenges - Bakkari, Mohammed A.; Moni, Sivakumar S.; Sultan, Muhammad Hadi; Madkhali, Osama A. (Recent Patents on Biotechnology, 2022)
The world continues to be in the midst of a distressing pandemic of coronavirus disease 2019 (COVID-19) infection caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), a novel virus with multiple antigenic systems. The virus enters via nasopharynx, oral and infects cells by the expression of the spike protein, and enters the lungs using the angiotensin-converting enzyme-2 receptor. The spectrum of specific immune responses to SARS-CoV-2 virus infection is increasingly challenging as frequent mutations have been reported and their antigen specificity varies accordingly. The development of monoclonal antibodies (mAbs) will have a more significant advantage in suppressing SARS-CoV-2 virus infectivity. Recently, mAbs have been developed to target included specific neutralizing antibodies against SARS-CoV-2 infection. The use of the therapeutic index of mAbs that can elicit neutralization by binding to the viral spike protein and suppress the cytokine network is a classic therapeutic approach for a potential cure. The development of mAbs against B-cell function as well as inhibition of the cytokine network has also been a focus in recent research. Recent studies have demonstrated the efficacy of mAbs as antibody cocktail preparations against SARS-CoV-2 infection. Target specific therapeutic accomplishment with mAbs, a milestone in the modern therapeutic age, can be used to achieve a specific therapeutic strategy to suppress SARS-CoV-2 virus infection. This review focuses on the molecular aspects of the cytokine network and antibody formation to better understand the development of mAbs against SARS- CoV-2 infection along with recent patents.
Keywords: cytokine storm